From Roman civitas to Anglo-Saxon shire : topographical studies on the formation of Wessex - Eagles, Bruce N. (Oxbow Books, 2018)
This book is the culmination of the author's lifelong interest in the Roman to medieval transition in England and in the analysis of the historic landscape of Wessex. It begins with a focused, referenced, and critical exploration of the thorny, but crucial, issues of post-Roman personal and group identity, employing linguistic, historical, archaeological and toponymical evidence. A series of integrated studies seek to elucidate changes in the territorial organisation of the Wessex landscape, from Somerset to Hampshire, from the Roman period to the emergence of the historic counties.